PENGARUH SENAM ZUMBA TERHADAP PENINGKATAN KEBUGARAN JASMANI ANAK-ANAK KOMPLEK MAJAPAHIT KOTA LUBUKLINGGAU - Wawan Syafutra; Sri Marwati; Windi Setiawan ($$8@@&&$%K, 2021)
The purpose of this study was to determine whether there is an effect of Zumba Gymnastics Exercise on increasing the physical fitness of children in the Majapahit complex, Lubuklinggau city, using a total sampling research design. The sample selected using the Random Sampling technique, amounting to 10 people. The data analysis used is statistical test - t. The instrument used in this study was a pedometer and a Pluit. The results of the initial test mean that 2 people with a time score of 18.45 are in the Poor classification (K). 3 people with a time score of 13.46 in the Moderate category (S) and as many as 5 people with a time score of 12.15 in the Good category (B). Then in the final test consisting of 2 people with a time score of 10.35 are in the Less category (K), 3 people with a time score of 13.00 are in the medium category (S), and as many as 5 people with a time score of 9.30 are in the good category (B). From these results there is a difference of 3 children with a t-count value of 7.679 and a t-table value of 2.0150 with a significance of 0.00 <0.05. So it can be concluded that the exercise method influences Zumba gymnastics on increasing the physical fitness of children in the Majapahit complex, Lubuklinggau